CD300 family receptors regulate eosinophil survival, chemotaxis, and effector functions. Issue 1 (21st December 2017) - Rozenberg, Perri; Reichman, Hadar; Moshkovits, Itay; Munitz, Ariel
Abstract: The CD300 family of receptors is an evolutionary conserved receptor family that belongs to the Ig superfamily and is expressed predominantly by the myeloid lineage. Over the past couple of years, accumulating data have shown that eosinophils express various Ig superfamily receptors that regulate key checkpoints in their biology including their maturation, transition from the bone marrow to the peripheral blood, migration, adhesion, survival, and effector functions in response to numerous activating signals such as IL-4, IL-33, and bacteria. In this review, we will present the emerging roles of CD300 family receptors and specifically CD300a and CD300f in the regulation of these eosinophil activities. The structure and expression pattern of these molecules will be discussed and their involvement in suppressing or co-activating eosinophil functions in health and disease will be illustrated. CD300 receptors can regulate key eosinophil functions in response to diverse stimuli. Therefore, CD300 family receptors may provide pharmacological targets for eosinophil-associated diseases.